Pengaruh Experiential Marketing dan Emotional Marketing Terhadap Loyalitas Pelanggan dengan Kepuasan Sebagai Variabel Intervening pada Platform E-Commerce Tokopedia - Aqmarina, Fauziah; Awali, Husni (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2023)
Introduction: This research aims to analyze the effect of experiential marketing and emotional marketing on the loyalty of generation Z Muslim customers through satisfaction on the Tokopedia e-commerce platform in Bandar District, Batang Regency. Research Methods: The analytical method used in this research is quantitative analysis method. The population in this study is Tokopedia's Muslim e-commerce customers belonging to Generation Z aged 20-24 years in Bandar District. The total population is 6,568 thousand people. Results: The results of this study indicate that experiential marketing and emotional marketing affect the loyalty of generation Z Muslim customers through satisfaction on the Tokopedia e-commerce platform in Bandar District, Batang Regency. Based on the research, it was found that the people of Bandar Sub-district belonging to Generation Z, aged 20-24 years, use Tokopedia continuously because they are influenced by the experiential marketing and emotional marketing strategies carried out by Tokopedia.